Fibin regulates cardiomyocyte hypertrophy and causes protein-aggregate-associated cardiomyopathy in vivo - Petersen, Matthias; Schmiedel, Nesrin; Dierck, Franziska; Hille, Susanne; Remes, Anca; Senger, Frauke; Schmidt, Inga; Lüllmann-Rauch, Renate; Müller, Oliver J.; Frank, Derk; Rangrez, Ashraf Y.; Frey, Norbert; et al. (Frontiers in Molecular Biosciences, 2023)
Despite the identification of numerous molecular pathways modulating cardiac hypertrophy its pathogenesis is not completely understood. In this study we define an unexpected role for Fibin (“fin bud initiation factor homolog”) in cardiomyocyte hypertrophy. Via gene expression profiling in hypertrophic murine hearts after transverse aortic constriction we found a significant induction of Fibin. Moreover, Fibin was upregulated in another mouse model of cardiac hypertrophy (calcineurin-transgenics) as well as in patients with dilated cardiomyopathy. Immunoflourescence microscopy revealed subcellular localization of Fibin at the sarcomeric z-disc. Overexpression of Fibin in neonatal rat ventricular cardiomyocytes revealed a strong anti-hypertrophic effect through inhibiting both, NFAT- and SRF-dependent signalling. In contrast, transgenic mice with cardiac-restricted overexpression of Fibin developed dilated cardiomyopathy, accompanied by induction of hypertrophy-associated genes. Moreover, Fibin overexpression accelerated the progression to heart failure in the presence of prohypertrophic stimuli such as pressure overload and calcineurin overexpression. Histological and ultrastructural analyses surprisingly showed large protein aggregates containing Fibin. On the molecular level, aggregate formation was accompanied by an induction of the unfolded protein response (UPR), subsequent UPR-mediated apoptosis and autophagy. Taken together, we identified Fibin as a novel potent negative regulator of cardiomyocyte hypertrophy in vitro. Yet, heart-specific Fibin overexpression in vivo causes development of a protein-aggregate-associated cardiomyopathy. Because of close similarities to myofibrillar myopathies, Fibin represents a candidate gene for cardiomyopathy and Fibin transgenic mice may provide additional mechanistic insight into aggregate formation in these diseases.